Potential of sugar beet vinasse as a feedstock for biocatalyst production within an integrated biorefinery context - Nurashikin, Binti Suhaili; Cárdenas‐Fernández, Max; Ward, John M.; Lye, Gary J. (Wiley Online Library, 2018)
BACKGROUND This work explores the feasibility of vinasse as an inexpensive feedstock for industrial biocatalyst production within the context of an integrated sugar beet biorefinery. As an exemplar, production of CV2025 ω‐Transaminase (ω‐TAm) in Escherichia coli BL21 was studied.